Analysis of Abnormal Returns Before and After the Announcement of the Merger of State-Owned Sharia Banks - Indah Amalia Putri; Ferry Khusnul Mubarok Mubarok; Rofiul Wahyudi (Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
AbstractPurpose - This study aims to examine the capital market's reaction to the merger of BUMN Syariah Banks, which is seen as abnormal returns at PT Bank BRI Syariah Tbk.Method - The data for this study were taken ten days before and ten days after announcing the BUMN Sharia Bank merger. The data was processed by paired sample t-test using SPSS.Result - Based on the analysis and discussion results, it shows that there is no market reaction to the announcement of the signing of the BUMN Islamic bank merger on BRIS shares as seen from the abnormal returns before and after the signing of the merger, which there is no significant difference.Implication - This can happen because the world is currently facing the COVID-19 pandemic, which causes market uncertainty. In addition, abnormal returns are not the only indicator to measure the wealth created by an event. Another factor that causes no significant difference in abnormal returns is that the data used in the event window research is daily and short enough to have no visible reaction. Furthermore, the issue of a merger has also been circulating before the announcement of the signingOriginality- This article examines abnormal returns before and after the announcement of the merger of State-Owned Sharia Banks